Foreignes on the Labour Market in the Czech Republic focused on Capital Prague - Částková, Veronika (2012)
This thesis deals with the position of foreigners in the labor market, focusing on the capital city of Prague. In the first part are identified and characterized the basic conceptstogether with the conditions for residence and employment. There is then analyzed sixselected countries, the most common nationalities registered by the labor office in Prague. They are always divided into 3 states of the EU, EHP and Switzerland for 3states from "third countries". The practical part analyzes the development of labor migration in the Czech Republic, particularly in Prague. The following individual chapters of labor migration are analyzed from different perspectives and division. The conclusion is devoted to analysis and subsequent evaluation of a questionnaire survey conducted among citizens of Prague and citizens who work in Prague. The aim of this study is to evaluate the overall situation of the status of foreigners in the labor market, further evaluation of the conditions of entry, residence and employment. The questionnaire is to confirm or refute hypotheses tent